2018
DOI: 10.1111/fog.12265
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic factors affecting interannual recruitment variability of Pacific saury (Cololabis saira) in the central and western North Pacific

Abstract: Pacific saury (Cololabis saira) has a short life span of 2 years and tends to exhibit marked population fluctuations. To examine the importance of sea surface temperature (SST) and mixed layer depth (MLD) as oceanographic factors for interannual variability of saury recruitment in early life history, we analyzed the relationship between abundance index (survey CPUE (catch per unit of effort)) of age‐1 fish and the oceanographic factors in the spawning and nursery grounds of the previous year when they were bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 35 publications
4
22
0
Order By: Relevance
“…1; partly overlapping with KESA), which is a winter spawning and nursery ground of saury, or by spring chlorophyll-a concentration (a proxy of prey for saury larvae) in the KOTZ and Kuroshio Extension (spring spawning and nursery grounds). The correlations between the survey-based CPUE and both winter SST and spring chlorophyll-a concentration were positive (Ichii et al 2018). The former correlation is consistent with that reported by Yasuda and Watanabe (2007) and partially consistent with that reported by Yatsu and Watanabe (2017).…”
Section: Pacific Saurysupporting
confidence: 91%
See 3 more Smart Citations
“…1; partly overlapping with KESA), which is a winter spawning and nursery ground of saury, or by spring chlorophyll-a concentration (a proxy of prey for saury larvae) in the KOTZ and Kuroshio Extension (spring spawning and nursery grounds). The correlations between the survey-based CPUE and both winter SST and spring chlorophyll-a concentration were positive (Ichii et al 2018). The former correlation is consistent with that reported by Yasuda and Watanabe (2007) and partially consistent with that reported by Yatsu and Watanabe (2017).…”
Section: Pacific Saurysupporting
confidence: 91%
“…The NPGO and sardine recruitment showed generally negative effects, and the relationship between the CPUE and February KESA SST anomaly was dome-shaped with a peak CPUE skewed positive toward the SST anomaly. Although a Rossby wave excited by NPGO propagates from the Central North Pacific to the Kuroshio area with a lag of 2-3 years (Di Lorenzo et al 2013), this lack of lag is consistent with the observed similarity in trajectories of CPUE and those of the relative abundance of Pacific saury estimated by a survey with drift nets in the Central North Pacific Ocean at longitudes of 170°E, 175°E, and 180°E, during June and July of 1979(Ichii et al 2018; hereafter called survey-based CPUE). These situations suggest that saury migrate from the Central North Pacific Ocean toward Hokkaido Island during summer, which is consistent with the summer migration patterns assumed by Suyama et al (2016).…”
Section: Pacific Saurysupporting
confidence: 74%
See 2 more Smart Citations
“…Pacific saury ( Cololabis saira , saury hereafter) is an oceanic species and one of the most important fishery stocks in the western North Pacific Ocean, characterized by the interannual and decadal‐scale variability of stock abundance (Figures 1 and 2; Anonymous, 2019 March; Ichii et al., 2018; Tian et al., 2004; Watanabe, 2009). The distribution of saury extends to the coastal areas of the North America, where saury has been incidentally caught (Anonymous, 2019 March).…”
Section: Introductionmentioning
confidence: 99%